Pelatihan Digital Marketing Produk Mie Mokaf Bagi Imigran Digital Pada Lembaga Masyarakat Desa Hutan “Sumber Makmur” - Purbowo, Purbowo; Chusnah, Miftachul; Magfiroh, Canggih Nailil (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Digital marketing training for digital immigrants is a challenge because you are dealing with people who were born before digital existed. This is different from digital natives, who have been using information and communication technology media since birth, such as smartphones and laptops. The service activity aims to introduce applicable digital marketing to digital immigrant community groups by using frequently used social media, namely Facebook. The material that has been delivered includes product photos, creating product descriptions, and uploading to Facebook. Participants are female forest farmers under the auspices of the Forest Village Community Institution (LMDH) "Sumber Pandan Makmur" located in Pandankrajan village, Kemlagi subdistrict, Mojokerto. The implementation methods used are lectures and practice. The training stages consist of a pre-test, lecture, practice and post-test. Participants' assessments use a scale between 1 and 9. The results of the implementation of service activities showed that the average pre-test score for activity participants is 4 out of 10, which means that people do not have sufficient insight into the training activities consisting of several stages, namely product photography, product descriptions, and uploading to Facebook social media. There was an increase at the end of the participant's post-test score, namely reaching 7.5 on a scale of 10, which means that participants had understood the material presented well and participants were able to practice photography, write descriptions and upload to Facebook social media. Based on the results of the paired T-test, it was stated that there was a significant difference between before and after participating in the training activities